Induction of noncatalytic TrkB neurotrophin receptors during axonal sprouting in the adult hippocampus - Beck, KD (J Neurosci, 1993)
Brain-derived neurotrophic factor (BDNF) and its signal transducing receptor, the TrkB tyrosine protein kinase, are expressed at high levels in the hippocampus of the adult brain, suggesting a role for BDNF mechanisms in neuronal plasticity. To test this hypothesis, we used defined lesions of perforant path and fimbria-fornix, two major hippocampal afferents, to remove synapses on dendrites of dentate gyrus granule cells and pyramidal cells of Ammon's horn and induce synaptic rearrangements. These combined lesions remove afferent connections from entorhinal cortex and septum and produce massive sprouting of axons of the commissural/associational pathways into the molecular layer of the hippocampal dentate gyrus. At days 1, 3, and 6, the lesions decreased BDNF mRNA expression ipsilaterally to approximately 50% of control, with complete recovery at 14 d. The lesions did not alter trkB mRNA levels in neuronal layers of the hippocampus; however, they resulted in a pronounced induction of trkB mRNA expression in hippocampal non- neuronal cells 6–14 d after lesioning. The induction corresponded in time and place to the synaptic reorganization in the lesioned hippocampus. The mRNA species newly induced by the lesions corresponded to those transcripts encoding the noncatalytic TrkB receptor isoform that lacks the cytoplasmic protein kinase domain. Expression of mRNAs coding for neurotrophin-3 and the TrkC tyrosine protein kinase were not altered by the lesions. The findings suggest that truncated noncatalytic TrkB molecules expressed on the surface of glial cells play an important role in plasticity of the adult brain, possibly regulating the concentration of bioactive neurotrophins or the responsiveness of neurotrophin receptors. Alternatively, they may play a role in presenting neurotrophin molecules to growing axons.